SEDIMENTATION STATUS OF LAKE VICTORIA: LOADING FROM RIVER MOUTH AND IN-LAKE SEDIMENTATION - Mwanuzi, F.; Rutagemwa, D. K.; Mathayo, A. (Tanzania Journal of Engineering and Technology, 2018)
Lake sediments consist of the input of suspended solids by river discharges, the autochthonous produced particulate matter in the water column and the settled material on the lake bottom. The loading, transport, formation and decay of the sediments entering the Lake Victoria from Tanzanian side was monitored for the period 2000 to 2005. The sedimentation study focused on; quantification of settling fluxes of particulate nutrients and organic carbon at the off- shore(Pelagic) and near-shore(Littoral) monitoring stations. Monitored data on sedimentation rate and settling velocities has been sampled and analysed in the period November 2000 to March 2005. The mean sedimentation rate at littoral stations for total particulate phosphorous (TPP) was about twice as compared to pelagic stations. The same situation was observed for total particulate carbon (TPC), however, total particulate silica did not show a clear pattern of variability between littoral and pelagic stations though there was a general tendency of decreasing towards the pelagic stations. Mean value for TPC /TPP sedimentation rate ratio was 117.61 for littoral and 90.74 for pelagic stations respectively compared to TBSi/TPP which was 3.15 for littoral and 2.10 for pelagic stations. The results show that sedimentation rates are highest at the littoral stations compared to pelagic stations. The differences in settling velocities indicate that the settling material consists dead and living material with a contribution of diatoms. The stoichiometric composition of the settling material indicates nitrogen limitation and a non-dominance of diatoms.